Future Regulation of Cross-Border Audiovisual Content Dissemination - Cole, Mark D.; Etteldorf, Christina (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The reality of cross-border dissemination of audiovisual content poses growing threats to the fundamental rights and values of the EU. In an increasingly complex network of sectoral EU legislation, including different institutional systems, the question of an effective reaction is pertinent. This study analyses the current legal framework for the cross-border dissemination of audiovisual content, focusing in particular on the country of origin mechanisms of the AVMS Directive, and identifies challenges in this respect for law enforcement. These are compared with approaches from other legal acts, such as the proposed European Media Freedom Act (EMFA), before possible solutions are presented.